2021
DOI: 10.1149/1945-7111/abf5f9
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Study of the Effect of High Salt Concentration on Uniform Corrosion of Carbon Steel in Aqueous CO2 Solutions

Abstract: Uniform C O 2 corrosion of carbon steel facilities is often a major problem when handling produced water in the oil and gas fields. High amounts of dissolved s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Nevertheless, with further increasing concentrations, 5–30% w/v, a decrease in corrosion rate was observed . Madani Sani et al, also found that under dynamic conditions, at 30 °C, corrosivity increased with NaCl concentration increase and reached a maximum rate at 1% wt NaCl then decreased at greater concentrations (3–20% wt)) attributed to NaCl impact on both CO 2 speciation and electrochemical processes . Fang et al similarly demonstrated that under dynamic conditions, at 20 °C, increasing NaCl concentration (3–25% wt) reduced the corrosivity as electrochemical processes were hindered .…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, with further increasing concentrations, 5–30% w/v, a decrease in corrosion rate was observed . Madani Sani et al, also found that under dynamic conditions, at 30 °C, corrosivity increased with NaCl concentration increase and reached a maximum rate at 1% wt NaCl then decreased at greater concentrations (3–20% wt)) attributed to NaCl impact on both CO 2 speciation and electrochemical processes . Fang et al similarly demonstrated that under dynamic conditions, at 20 °C, increasing NaCl concentration (3–25% wt) reduced the corrosivity as electrochemical processes were hindered .…”
Section: Introductionmentioning
confidence: 93%
“…32 Madani Sani et al, also found that under dynamic conditions, at 30 °C, corrosivity increased with NaCl concentration increase and reached a maximum rate at 1% wt NaCl then decreased at greater concentrations (3−20% wt)) attributed to NaCl impact on both CO 2 speciation and electrochemical processes. 33 Fang et al similarly demonstrated that under dynamic conditions, at 20 °C, increasing NaCl concentration (3−25% wt) reduced the corrosivity as electrochemical processes were hindered. 34 At relatively higher temperatures (i.e., 80 °C), studies generally suggest that, under static conditions, corrosion rates decreased with increasing NaCl concentration (1−10 wt %) for pH <6.6.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Experimental values for K ca were determined by collecting measured pH over different temperatures (5–80 °C) in solutions containing dissolved CO 2 (0.53–0.99 bar) and with various salt concentrations (0.1–25 wt %) from the literature. ,, Equation is plotted against I 0.5 as dots in Figure , where the dotted line is the best fit obtained over the entire range of temperature selected. As can be seen from the figure, rather than the quadratic correlation with I 0.5 as suggested by eq , as well as proposed by the expressions of Oddo and Tomson and Gao, the best fit involves a linear dependency with I 0.5 .…”
Section: Improvement To Water Speciation In Co2 Environmentsmentioning
confidence: 99%
“…Figure4. pH comparison between model calculations7 and experimental results12,36,37 at different temperatures.…”
mentioning
confidence: 99%